Monopsony capitalism power and production in the twilight of the sweatshop age - Kumar, Ashok 1984- (Cambridge University Press, 2020)
"Monopsony Capitalism explores the combination of capital's changing composition and labour's subjective agency to examine whether the waning days of the 'sweatshop' have indeed begun. Focused on the garment and footwear sectors - which epitomize the leading edges in the advance of globalization and the spread of vertically disintegrated value chains - the book introduces a universal logic that governs competition and reshapes the chain. Simply put, deregulation produces high degrees of monopsony power, increasing the value share for the lead firm. This intensifies competition, exerts downward pressure, and winnows the number of suppliers able to compete. The result is supplier-end consolidation. Consolidation increases the surviving suppliers' share of value, which expands access to finance, facilitates self-investment, and raises entry barriers.
Includes bibliographical references and index
Keywords: Kapitalismus / (DE-627)091370035 / (DE-2867)11046-0; Monopson / (DE-627)091378745 / (DE-2867)10206-2; Sozialstandards / (DE-627)091368383 / (DE-2867)19509-2; Arbeiterbewegung / (DE-627)091347351 / (DE-2867)16387-5; Textilindustrie / (DE-627)091394791 / (DE-2867)13145-2; Internationale Wirtschaft / (DE-627)091348722 / (DE-2867)10605-2; USA / (DE-627)091396867 / (DE-2867)17829-1; Welt / (DE-627)09140004X / (DE-2867)16809-5; Sweatshops / Developing countries; Clothing trade / Developing countries; Clothing workers / Labor unions / Developing countries; Monopsonies; Capitalism